2011
DOI: 10.2903/j.efsa.2011.2428
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on application (EFSA‐GMO‐CZ‐2008‐54) for placing on the market of genetically modified insect resistant and herbicide tolerant maize MON 88017 for cultivation under Regulation (EC) No 1829/2003 from Monsanto

Abstract: This Scientific Opinion reports on an evaluation of a risk assessment for placing on the market of genetically modified maize MON 88017 for cultivation. The EFSA GMO Panel considers that maize MON 88017 is unlikely to have any adverse effect on the environment, except for the possible resistance evolution to the Cry3Bb1 protein in coleopteran target pests; resistance evolution may lead to altered pest control practices that may cause adverse environmental effects. The cultivation management of maize MON 88017 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 676 publications
(902 reference statements)
0
5
0
Order By: Relevance
“…The Cry3Bb1 protein has been previously assessed by the GMO Panel (e.g. EFSA GMO Panel 2009, 2011c and no safety concerns for humans and animals were identified. Updated bioinformatics analysis did not reveal similarities of the Cry3Bb1 protein to known toxins causing toxicity to humans and animals (except for Coleoptera).…”
Section: Testing Of the Newly Expressed Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Cry3Bb1 protein has been previously assessed by the GMO Panel (e.g. EFSA GMO Panel 2009, 2011c and no safety concerns for humans and animals were identified. Updated bioinformatics analysis did not reveal similarities of the Cry3Bb1 protein to known toxins causing toxicity to humans and animals (except for Coleoptera).…”
Section: Testing Of the Newly Expressed Proteinsmentioning
confidence: 99%
“…The GMO Panel has previously evaluated the safety of the Cry3Bb1 and CP4 EPSPS proteins in the context of other applications and no concerns on allergenicity were identified (e.g. EFSA GMO Panel, 2009, 2011c.…”
Section: Assessment Of Allergenicity Of the Newly Expressed Proteins 49mentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of statistically significant differences in turn, however, is then deemed by the EFSA panel sufficient to declare the new GM plant comparatively as safe as the non-GM counterparts. But even if significant differences between the measured biochemical compounds are reported that also regularly exceed even historical ranges, these differences are interpreted away as being biologically irrelevant (e.g., see case examples [70][71][72][73]).…”
Section: Including Unrelated Reference 'Controls'mentioning
confidence: 99%
“…The EFSA panel has subsequently used this 'comparative (safety) assessment' step for GM plants and GM food and feed, as an opportunity to declare the many reported statistically significant differences found among the chemical analytical data (called 'compositional analyses' or 'comparative analyses of the composition') to be 'not biological relevant' , so long as the reported values fall within the 'natural variation' of 'traditionally cultivated crops' , i.e., data derived from any non-GM varieties ever analyzed in history as long as they may share common pedigree (e.g., [70][71][72]): "The potential variability in the degree of genetic similarity between the GM plant and its comparator(s) does not necessarily compromise the reliability of the safety assessment, provided that the comparator is genetically "as close as possible" to the GM plant with regard to its breeding pedigree. " [17].…”
Section: Re-introducing the Concept Of 'Substantial Equivalence' Into Eu Risk Assessment By Renaming It A 'Comparative Safety Assessment'mentioning
confidence: 99%